Representações sociais de família para um grupo de professoras do ensino fundamental da cidade de Araguari-MG - Silva, Ana Lucia Costa e (2005)
Giving credit itself that the professor has a basic paper in the formation of the individual, one became excellent to know which are the representations concerning family, that its thought so that if it can have one better understanding of its teaching action. This study it had as objective to identify the social representations of a group of teachers of basic education concerning the thematic family, from four called situations "routine situations". The situations had been presented the 16 teachers of the four initial series, basic education, that act as regents in the municipal schools of the city of Araguari-MG, and could have been identified as: pertaining to school daily situation, situation notice, letter of music "Family" of the group Titãs and Álbum of the Families, elaborated from clippings of magazines and periodicals. The situations had been applied in the school where the teachers acted, during the schedule of module of the same ones, so that they could read the instruments and proceed to its reply. The result gotten with the use of the four cited instruments made possible, exactly in virtue to offer differentiated languages, that the social representations of family for this group of teachers were known and that we concluded that the teachers are few who had obtained to perceive the different familiar organizations that if make gifts in our context, while the majority still visualizes the family traditional as standard of familiar behavior to be followed. It is suggested, from the data gotten with the accomplishment of the research, a reflection regarding a reorganization in the courses of teaching formation so that the teachers obtain to become more critical in relation pedagogical practical its. One gives credit that this research opens ways so that the subject family boarded and is argued under other vertices, as Sociology, Anthropology, and still inside of proper Psychology, as well as it offers support for the accomplishment of project of intervention capable to mobilize and to sensetize the teachers so that they can review its performance pedagogical, taking the knowledge concerning the familiar dynamics of its pupils as control point for its work in classroom.